Zebrafish Models for Dyslipidemia and Atherosclerosis Research - Schlegel, Amnon (Frontiers in Endocrinology, 2016)
Atherosclerotic cardiovascular disease is the leading cause of death. Elevated circulating concentrations of lipids are a central pathogenetic driver of atherosclerosis. While numerous effective therapies for this condition have been developed there is substantial unmet need for this pandemic illness. Here I will review nutritional, physiological, genetic and pathological discoveries in the emerging zebrafish model for studying dyslipidemia and atherosclerosis. The technical and physiological advantages and the pharmacological potential of this organism for discovery and validation of dyslipidemia and atherosclerosis targets are stressed through summary of recent findings. An emerging literature shows that zebrafish, through retention of a cetp ortholog gene and high sensitivity to ingestion of excess cholesterol, rapidly develop hypercholesterolemia, with a pattern of distribution of lipid species in lipoprotein particles similar to humans. Furthermore, recent studies leveraging the optical transparency of zebrafish larvae to monitor the fate of these ingested lipids have provided exciting insights to the development of dyslipidemia and atherosclerosis. Future directions for investigation are considered, with particular attention to the potential for in vivo cell biological study of atherosclerotic plaques.